....................................................

Algebra
Tutor: None Selected Time limit: 1 Day

Apr 21st, 2015

2x - y = 5

x = 2y - 2

Now put the value of x in first then

2(2y - 2) - y = 5

4y - 4 - y = 5

3y - 4 = 5

3y = 9

y = 3

For x

x = 2(3) - 2

x = 6 - 2

x = 4 

Hence (x,y) = (4,3)

Apr 21st, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Apr 21st, 2015
...
Apr 21st, 2015
Dec 5th, 2016
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer